Psychological and criminal legal aspects of suicidal behavior - Arzikulov, Utkirbek (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
This article reviews the psychological and criminal aspects of suicidal behavior, determining the cause of suicide, the two main stagesof assessing suicide, the condemnation of suicidal acts by law scholars, and the fact that suicide is currently a socially dangerous crime, that in all CIS countries and in our Republic, bringing a person to suicide entails criminal liability